2012
DOI: 10.1007/s10616-012-9444-3
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effect of the egg wax of Amblyomma cajennense (Acari: Ixodidae)

Abstract: The control of viral infections,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…In the studies carried out to determine the antimicrobial activities of the wax, successful results have been obtained in various degrees against different agents such as Escherichia coli (22,29), Staphylococcus epidermidis (25)(26)(27)32), Staphylococcus aureus (22,26,29), Serratia marcescens (25), Bacillus cereus (26), Bacillus subtilis (25)(26)(27), Micrococcus luteus (27,29,30), Pseudomonas aeruginosa (22,31), Enterecoccus faecalis, Enterecoccus faecium, Nocardia asteroides, Salmonella enteritidis, Klebsiella pneumonia (22), picornavirus (28), and influenza virus (28,29). Furthermore, the wax of Boophilus microplus was reported to be effective on C. albicans to some extent (30), and the wax of Rhipicephalus sanguineus was found to be effective on the same agent (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies carried out to determine the antimicrobial activities of the wax, successful results have been obtained in various degrees against different agents such as Escherichia coli (22,29), Staphylococcus epidermidis (25)(26)(27)32), Staphylococcus aureus (22,26,29), Serratia marcescens (25), Bacillus cereus (26), Bacillus subtilis (25)(26)(27), Micrococcus luteus (27,29,30), Pseudomonas aeruginosa (22,31), Enterecoccus faecalis, Enterecoccus faecium, Nocardia asteroides, Salmonella enteritidis, Klebsiella pneumonia (22), picornavirus (28), and influenza virus (28,29). Furthermore, the wax of Boophilus microplus was reported to be effective on C. albicans to some extent (30), and the wax of Rhipicephalus sanguineus was found to be effective on the same agent (29).…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, the egg waxes of Amblyomma habreum (25,26) A. cajennense (27)(28)(29), A. aureolatum (29), Boophilus (Rhipicephalus) microplus (29-32), Rhipicephalus sanguineus (29), Haemaphysalis longicornis, H. doenitzi, Dermacentor silvarum and Hyalomma asiaticum (22) have been tested against various bacteria, fungi, and viruses, and some considerable results were obtained. However, these studies have also revealed that the antimicrobial efficacy of the wax varies dramatically related to the tick species.…”
Section: Introductionmentioning
confidence: 99%
“…Other peptide, isolated from a marine sponge Petromica citrine, has showed an antiviral activity of against bovine viral diarrhea vírus (Bastos et al, 2013). Lima-Netto et al, 2012, observed the antiviral effect of eggs wax from tick Amblyomma cajennense against influenza and picornavirus, for influenza virus, in this case, an amount as small as 12 μg/mL from a crude suspension of egg wax was able to reduce in 128 UHA (hemaglutinant unit) of influenza virus (H1N1). With picornavirus, this reduction was of 256-fold.…”
Section: Discussionmentioning
confidence: 94%
“…Carmo et al, 2012) describes a system for the protein expression in Sf9/baculovirus cells using the recombinant DNA to obtain a protein from the L. obliqua caterpillar that displays a potent antiviral action obtained by Greco et al, 2009. Recently, our group has studied the presence of antiviral agents in diferents animals source (Lima-Netto et al, 2012., Carmo et al, 2015, Toledo-Piza et al, 2016, 2018; Carvalho et al, 2017; Coelho et al, 2015, 2018). So, the objectives of this work were the identification and isolation of antiviral substances in hemolymph from Podalia sp and M. Albicolis ( Lepidoptera: Megalopigydae )…”
Section: Introductionmentioning
confidence: 99%
“…Recentemente, nosso grupo tem demonstrado a presença de proteínas com alto potencial antiviral e antimicrobiano na cera de ovos de carrapatos Amblyomma cajennense (DE LIMA-NETTO et al, 2012;LIMA-NETTO et al, 2011) e na hemolinfa de Lonomia obliqua (GRECO et al, 2009). Cultivos de células de inseto suplementado com hemolinfa de L. obliqua tiveram sua longevidade aumentada (MARANGA et al, 2003).…”
Section: Lista De Abreviaturas E Siglasunclassified